Venous thromboembolism leading to diagnosis of de novo malignancy in an organ transplant recipient. (8th September 2018) - Mitchell, Natalie; Connell, Alana; Kurth, Benjamin
Abstract : We report the case of a patient with remote orthotopic liver transplant who was ultimately diagnosed with Merkel cell carcinoma following admission for initial venous thromboembolism. Additionally, we review pertinent literature related to the risk of skin cancer in solid organ transplant recipients and discuss the importance of yearly skin exams in this patient population.